Path Analysis of the Influence of Students Variables and School Location on Students’ Academic Achievement in Economics - Ngozi Obiorah, Juliana; Dorathy Eneogu, Njideka; A. Nji, Ifeyinwa; G. Ezeocha, Ihechi; O, Idika, Ezinne; Ekwesaranna, Fumnanya; A.D Nwabufo, Chibuzo (International Journal of Psychosocial Rehabilitation, 2024)
The study sought to determine path analysis of the influence of student variables and school location on senior secondary students’ academic achievement in Economics. Two research questions and two hypotheses guided the study. The study adopted a correlational survey design. Sample of the study consist of 377 SS2 Economics students drawn from 82 secondary schools in Ogoja Education Zone of Cross River State. Multi-staged sampling procedure was used to select fifteen schools from the urban and rural stratum. Two instruments were used for data collection namely; Students Variable Questionnaire (SVQ) and Proforma for collecting SS2 Economics Students’ Scores for first term 2018/2019 academic session. Face and construct validity were employed in validating the instruments and were also tested for reliability. Using Cronbach Alpha reliability estimate the internal consistency, 0.94 for SVQ. Data collected were analyzed using IBM AMOS. Hypotheses were tested using Chi-square Goodness of Fit Index (CGFI), Root Mean Square Error of Approximation (RMSEA) and ANOVA. Result shows there are 7 significant causal paths out of the 9 originally designed. Also, the student variables and school location have combined influence on students’ academic achievement in Economics. However, there is no significant model fit for explaining students’ academic achievements in Economics based on the exogenous variables. Based on the findings, it was concluded that student variables and school location have high positive influence on students’ academic achievement in Economics. It was recommended that Students should be motivated and encouraged to learn through using teaching methods that increase the interest and curiosity of students to learn Economics.